Habitat Improvement In Effort To Conservation Insect Diversity And Natural Enemies On Potato Cultivation - Sidauruk, Lamria; Panjaitan, Ernitha; Romauli Panataria, Lince; Sipayung, Patricius (Politeknik Negeri Lampung., 2024)
This study aimed to determine the habitat approach on potato cultivation to increase diversity of insects. Habitat improvement design by agricultural system and planting system on different season. This study consisted of two experiments. The first done at planting season from March to July (dry season) and the second done at planting season from October to January (rainy season). Research designed by Split plot design with main plot are farming systems (inorganic farming and organic farming) and the subplot are the design of cropping system (sole potato; potato and cabbage; potato and mustard; potato and onion). The data was analyzed by ANOVA and Tukey test. The result showed that planting season from March to July (dry season) as well as the planting season from October to January (rainy season) showed that insect diversity index, predator population and parasitoid population were higher in organic farming compared to inorganic farming systems. The design of cropping system significantly affect insect diversity index,natural enemies population such as predator Coccinelids and parasitoid Braconid wasp and M. persicae population. In organic farming, intercropping potato with cabbage found the highest insect diversity index and the highest population of parasitoid Braconid wasp and the lowest population of M. persicae. The highest population of predator Coccinelids found at interropping potato with mustard. Combined analysis of the planting on dry season and rainy season showed that insect diversity index and population of parasitoid Baraconid wasp not significantly difference between planting on dry planting and planting on rainy season. On the other hand, population of predator Coccinellids and M. persicae significantly more higher at planting on dry season than planting on rainy season.